Prevalence and risk factors of seizure in children with acute bacterial meningitis: an update epidemiologic study - Ataei Nakhaei, Alireza; Bakhtiari, Elham; Ghahremani, Sara; Akhondian, Javad; sasan, Mohammad Saeed; movahed, Malihe; Aelami, Mohammad Hasan (Iranian Journal of Child Neurology, 2021)
Abstract Objective The current study aimed to investigate the prevalence and risk factors of seizure in acute bacterial meningitis. Materials & Methods In the present study, a total of 180 children (age range, 2 months to 14 years) with acute bacterial meningitis, were separated into two groups based on the diagnosis of seizure. The study was conducted in Mashhad (Iran) from 2002 to 2016. Results Seizure occurred in 37.4% of children with bacterial meningitis. Streptococcus pneumonia (S. pneumonia) was the most common organism. Most of the children with seizures (53.7%) had more than one episode. Also, 35% of patients had neurologic complications. Complications were more related to the seizure occurrence, the number of episodes, prolonged seizure, and being younger than 12 months. Age categories of less than 1 year and 1-5 year were associated with increased risk of seizure (odds ratio: 4.33 and 6.54, respectively). The more episode of seizure was associated with more complications (odds ratio: 6.33). Conclusion The prevalence of seizure in acute bacterial meningitis was 37.4%. Because of association between seizure and complication, it is necessary to pay more attention to the exact and on-time diagnosis of bacterial meningitis.